Investigation of Sickle‐Cell Haemoglobin Polymerisation under Electrochemical Control. Issue 10 (23rd May 2013) - Iqbal, Zeshan; Li, Matthew; McKendry, Rachel; Horton, Michael; Caruana, Daren J.
Abstract We describe an electrochemistry‐based technique to control and monitor the polymerisation of sickle‐cell haemoglobin (HbS). The polymerisation was monitored as a change in turbidity during the depletion of oxygen in a small volume custom‐built thin‐layer electrochemical cell. The cell allowed the investigation of HbS polymerisation as a function of HbS concentration, temperature and solution pH. We confirm that the oxygen was efficiently depleted using finite‐element modelling to accurately recreate the electrochemical thin‐layer cell. Understanding the nucleation and growth of HbS polymerisation will provide a better understanding of the pathophysiology of sickle‐cell disease in vivo, and thus help improve therapeutic strategies for this common and frequently disabling disorder.